PERLINDUNGAN HUKUM BAGI PEMEGANG SERTIFIKAT HAK MILIK ATAS TANAH DALAM KETENTUAN PASAL 32 AYAT (2) PP No. 24 TAHUN 1997 - Putu Ade Harriestha Martana (University of Udayana, 2014)
The title of this study is “legal protection for land ownership right certificate holder according to Article 32 clause (2) Government Regulation Number 24 Year 1997”. There is a contradiction between the negative publication system which is adopted in Indonesian land registration system and the indefeasable title that is given after the certificate is published for more than five years according to Article 32 clause (2) Government Regulation Number 24 Year 1997 about Land Registration. Therefore some issues are occured, which is the legal certainty and legal protection of the land ownership right certificate holder after the five years period according to Article 32 clause (2) Government Regulation Number 24 Year 1997. The research method used in this study is normative legal research focusing on investigation of legislature as the primary legal material and supported with the legal doctrine as secondary legal material. The approaching methods used is legal concepts approach and statute approach. From the legal material research can be concluded that in normative basis the aim of article 32 clause (2) Government Regulation Number 24 year 1997 is to give a legal protection and legal certainty, but in the process the article is contradictory to the negative publication system and the clauses in the article itself is contradictory, therefore it does not give adequate legal protection and legal certainty for the holder of the land ownership right certificate after the five years period.